HSP 72 expression and antioxidant enzymes in Murrah buffaloes during heat exposure in climatic chamber - LALLAWMKIMI, MICHELLE C; SINGH, S V; DE, S; HOODA, O K; UPADHYAY, R C; SINGH, A K; VAIDYA, M M (The Indian Journal of Animal Sciences, 2012)
Present investigation was undertaken to monitor the level of HSP-72 mRNA expression in lymphocyte and antioxidant enzymes in RBC lysate during exposure in climatic chamber. Six each of growing (6–12 months), heifer (2–2.5 years) and lactating (2–3parity) Murrah buffaloes were selected from the NDRI herd and exposed at 2 different conditions, viz. exposure I (38±1°C with 50±2%RH) and exposure II (42±1°C with 40±2% RH) in climatic chamber for 3 h continuously. Blood samples were collected prior to exposure, at hourly interval during exposure and after end of 3 h of exposure. The levels of erythrocyte SOD and catalase increased significantly in all experimental groups after 3 h of exposures. The magnitude of increase in SOD and catalase was significantly higher at exposure II compared to exposure I in all groups of animals. The HSP72 mRNA expressions increased significantly after end of 3 h of exposures in growing and heifers of Murrah buffaloes during both exposure I and II whereas in lactating buffaloes the HSP72 mRNA expressions increased during first 2 h of exposures and later on a declining trend was observed at third hour. The magnitude of increase in HSP 72 mRNA expression was significantly higher during exposure II compared to exposure I in all groups of animals. The levels of HSP 72 mRNA expression and antioxidant enzymes increased with the increase in temperature indicating an oxidative stress. Therefore, the Murrah buffaloes need to be protected from extreme heat stress (42°C) to maintain homeostasis and oxidative status within the physiological limits to sustain the productivity.